Analisis Strategi Keunggulan Bersaing Usaha Penjahit Rumahan dengan Pendekatan Analisis SWOT : Studi Kasus pada Usaha Jahit Ibu Mersi di Desa Habi - Theresia Novita Maristela; Wilhelmina Mitan; Emilianus Eo Kutu Goo (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
This research aimed to analyze the competitive advantage strategy applied by Mrs. Mersi as a sewing business actor and the strategies carried out based on the SWOT analysis approach in Mrs. Mersi’s home tailoring business in Habi Village. This research data was obtained from interviews, observations, distributing questionnaires, and documentation. The findings of this research indicated that the Competitive Advantage Strategy applied by Mrs. Mersi consisted of low sewing rates, diverse products produced, and the ability to meet customer needs following the budget. Meanwhile, based on the SWOT analysis, the value (X,Y) = (0,3, -0,4). So Mrs. Mersi’s sewing business was included in quadrant II (Positive, Negative) which included a Diversification Strategy. Thus the strategy that needs to be pursued by Mrs. Mersi is to expand the sewing room or make a special room for sewing, improve more modern / sophisticated equipment, and do promotions.